PEREMPUAN DAN PERANNYA DALAM PEMBANGUNAN KESEJAHTERAAN SOSIAL (WOMEN AND ITS ROLE ON SOCIAL WELFARE DEVELOPMENT) - Ratih Probosiwi (NATAPRAJA, 2015)
Women are seen as second class citizens. The role of women in development is often questionable as being unfit and incapable. This paper attempts to analyze the gender is not only limited to the role and activities of men and women, but also their relationship. It also examines women in development, the role, position, and also increase its role in development. This paper emphasizes the empowerment of women in development, especially the development of social welfare. Enterprises group considered suitable for women, although potentially reducing the self-power. This paper is literature review through search of data and information from books, scientific articles, journal, gender-related laws, and policies that tie. It’s required gender mainstreaming policies and involved women in development. This policy will ensure that women are able to survive and carry out its social function properly.Keywords: Women, Discrimination, Development, and Gender Mainstreaming